Flood Management And Inundation Mapping: A Case Study Of Khando River Basin Of Saptari District, Nepal - Chaudhary, Kishor Kumar; Dahal, Khet Raj; Parajuli, Ramesh (International Journal on Engineering Technology, 2026)
Flooding is increasingly recognized as one of the wede168 most significant water-related hazards globally. The extent of damage inflicted on various components escalates over time. This study aims to examine the frequency of flooding, develop flood maps for the Khando River Basin corresponding to various recovery periods, and pinpoint hazardous areas within the basin. The Khando River Basin, encompassing an area of 117.3 km², has been selected for this analysis. Frequency analysis is conducted utilizing the Gumbel calculation method alongside HEC-RAS software. The creation of Flood Hazard Maps is essential for assessing flood levels. These maps were generated using HEC-RAS version 5.0.7 and integrated with ArcGIS 10.1 and HEC-GeoRAS extensions. A Digital Elevation Model (DEM) with a spatial resolution of 20 m × 20 m was employed for the research. The discharge data utilized in this study have been validated against field measurements. Discharge and flood depth increased with return periods (2–100 years), reaching 3 m at the 100-year event in the Chure Range, where shorter cross-sections had greater depths, while other areas showed lower depths. Flood depths in the Khando River were classified as high, medium, and low risk by the Department of Hydrology and Meteorology (DHM). The flood zone indicates population vulnerability, making this study helpful in valuable study for planning and managing future natural disasters.